Pengaruh Model Pembelajaran Picture and Picture Berbantuan Media Wordwall terhadap Hasil Belajar Siswa pada Materi Norma dan Aturan Kelas IV SD Negeri Garot Aceh Besar - Nasyifa, hafizatul; Safiah, Intan; Nurmasyitah, Nurmasyitah (Universitas Jambi, 2026)
The low learning outcomes of students on the material of norms and rules and the less than optimal use of learning models and interactive media cause students to have difficulty understanding the material. Learning that is still centered on the teacher also makes students less active, resulting in low learning outcomes. This study aims to determine the effect of the picture and picture learning model assisted by wordwall media on student learning outcomes on the material of norms and rules of grade IV SD Negeri Garot Aceh Besar. This study uses a quantitative approach with a quasi-experimental type and a nonequivalent control group design. The research sample consists of class IV C as the experimental class and class IV A as the control class. Data were collected through pretest and posttest tests, then analyzed using the N-gain test, normality test, homogeneity test, and Independent Samples t-Test. The results of the study showed that the average learning outcomes of students in the experimental class were higher than those in the control class. The results of the Independent Samples t-Test showed a significance value of 0.007 <0.05, so it can be concluded that the picture and picture learning model assisted by wordwall media has a significant effect on student learning outcomes.